Principles of Soil Conservation and Management - Blanco-Canqui, Humberto; Lal, Rattan (Springer Netherlands : Imprint: Springer, 2008)
"Principles of Soil Management and Conservation" comprehensively reviews the state-of-knowledge on soil erosion and management. It discusses in detail soil conservation topics in relation to soil productivity, environment quality, and agronomic production. It addresses the implications of soil erosion with emphasis on global hotspots and synthesizes available from developed and developing countries. It also critically reviews information on no-till management, organic farming, crop residue management for industrial uses, conservation buffers (e.g., grass buffers, agroforestry systems), and the problem of hypoxia in the Gulf of Mexico and in other regions. This book uniquely addresses the global issues including carbon sequestration, net emissions of CO2, and erosion as a sink or source of C under different scenarios of soil management. It also deliberates the implications of the projected global warming on soil erosion and vice versa. The concern about global food security in relation to soil erosion and strategies for confronting the remaining problems in soil management and conservation are specifically addressed. This volume is suitable for both undergraduate and graduate students interested in understanding the principles of soil conservation and management. The book is also useful for practitioners, extension agents, soil conservationists, and policymakers as an important reference material.